2017
DOI: 10.1007/s10495-017-1390-2
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Fluoxetine induces apoptosis through endoplasmic reticulum stress via mitogen-activated protein kinase activation and histone hyperacetylation in SK-N-BE(2)-M17 human neuroblastoma cells

Abstract: Fluoxetine (FLX) is an antidepressant drug that belongs to the class of selective serotonin reuptake inhibitors. FLX is known to induce apoptosis in multiple types of cancer cells. In this study, the molecular mechanisms underlying the anti-cancer effects of FLX were investigated in SK-N-BE(2)-M17 human neuroblastoma cells. FLX induced apoptotic cell death, activation of caspase-4, -9, and -3, and expression of endoplasmic reticulum (ER) stress-associated proteins, including C/EBP homologous protein (CHOP). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 55 publications
3
13
0
Order By: Relevance
“…Intriguingly, the responses of the other two MAPK members, ERK and JNK, to indomethacin were far less than that observed with p38. Despite the discrepancy, biochemical findings suggested a potential involvement of ER stress in the regulation of p38 signaling since the MAPK upstream kinase Ask1 and free radicals correlated well with ER stress [31,32,35]. This was confirmed by our subsequent findings that showed indomethacin increased protein phosphorylation of PERK and eIF2α, and protein expression of CHOP, indicating the induction of ER stress.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Intriguingly, the responses of the other two MAPK members, ERK and JNK, to indomethacin were far less than that observed with p38. Despite the discrepancy, biochemical findings suggested a potential involvement of ER stress in the regulation of p38 signaling since the MAPK upstream kinase Ask1 and free radicals correlated well with ER stress [31,32,35]. This was confirmed by our subsequent findings that showed indomethacin increased protein phosphorylation of PERK and eIF2α, and protein expression of CHOP, indicating the induction of ER stress.…”
Section: Discussionsupporting
confidence: 68%
“…The generation of reactive oxygen species and mobilization of cytosolic free Ca 2+ are consequences of ER stress, and oxidative stress also acts as an inducer of ER stress [31,32,35]. Elevated levels of reactive oxygen species and cytosolic free Ca 2+ were found in indomethacin-treated glioma cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prozac did not cause significant changes in cell cycling activity, but it induced a significant increase of DNA fragmentation in the CKS1/MYC high cell lines Kelly and SKNAS compared to CKS1/MYC low hNB and BJ (Supplementary figure 2). The hypothesis that Prozac might cause apoptosis of neuroblastoma cells is corroborated by a recent study showing that the MYCN-amplified SK-N-BE 2 cell line undergoes apoptosis in the presence of the drug 18 . The selected neuroblastoma cell lines were cultured in the presence of increasing concentrations of Prozac and subjected to western blot analysis with a p27 antibody.…”
Section: Prozac Inhibits Short and Long-term Growth Of Neuroblastoma mentioning
confidence: 80%
“…Typically, SSRIs are used to treat depression, and FLX is one of the most widely used drugs in this category with fewer side effects compared to other antidepressants [5,26]. Studies reported that FLX might affect fetus development, cancer, apoptosis, inflammation, neurogenesis, neuronal maturation, changes in neurotransmitters (glutamate and noradrenaline), cell proliferation and differentiation [27][28][29][30][31][32][33][34]. In this study, the effects of FLX on proliferation and differentiation of human ADSCs were investigated.…”
Section: Discussionmentioning
confidence: 99%